THE MODERN MELTING EQUIPMENT OF THE CENTRAL FREQUENCY OF THE FIRM OTTO JUNKER. HIGH CAPACITY, EFFICIENCY AND FLEXIBILITY - V. Kobusinnskij; E. Stanek (Литьë и металлургия, 2004)
The modem melting equipment of central frequency the firm OTTO JUNKER is presented.